The social capital in the various forms of public limited company, principles and various functions that it complies both externally and internally in these - Walde Jáuregui, Vicente Rodolfo (2011)
Inside the mercantile system, the joint-stock company is relevant, evidenced by a historical analysis of this corporate form. This is worthy of a special legal regulation as contract type of company; currently reaching great diversification, influence and development under various corporate forms. The joint stock company thus becomes a legal figure that rests on the concept of «capital» which is his essence, term whose understanding is based on the distinction between «patrimony» and «social capital»; social capital that is governed by the principles of determination and unity of the Social Capital, and stability of Capital, those who complete the defence of the capital of the company by shares, with which it is intended to give adequate protection to the business.